Perinatal protein deprivation facilitates accumbal ERK phosphorylation in cocaine-sensitized adult rats - Velazquez, Evelin Edith (2013)
In previous studies we described that perinatal protein deprivation facilitates the development and expression of behavioral sensitization to cocaine. In this research, we explored whether the increased reactivity observed in deprived (D) versus control (C) rats is also evident during drug-free withdrawal periods. Considering that activation of the extracellular signal-regulated protein kinase (ERK) is suggested to be involved in cocaine-induced behavioral sensitization, we study the effects of perinatal protein deprivation on phosphorylated ERK2 (pERK2) protein levels in the NAc (core and shell) during different drug-free withdrawal periods. To induce behavioral sensitization, C- and D-rats received a daily injection of cocaine (5-10. mg/kg, i.p.) for 7 days and locomotor activity was performed on days 1 and 7. Cocaine-sensitized animals were left drug-free and pERK2 was assessed on withdrawal days (WD) 1, 4, 7 and 21. In the NAc core, cocaine induced ERK signaling pathway activation in a dose-dependent manner, and only D-rats showed a significant increase in pERK2 protein levels with the lowest dose of cocaine (5. mg/kg). Moreover, sensitized C-rats with 10. mg/kg showed an increase in pERK2 levels from WD7 while D-rats showed this activation on WD4, which remained increased on WD7 and 21. In contrast, in the NAc shell, only sensitized D-rats with cocaine 10. mg/kg showed ERK2 activation on WD21. These results suggest that perinatal protein deprivation facilitates the molecular processes involved in neuronal plasticity occurring during withdrawal.